Groundwater in Makhmour District and its Investments: (A Study in Natural Geography) - A., Sozan M. (Al-Adab Journal, 2022)
Groundwater occupies a leading place in areas where there is no surface runoff from streams and rivers, so it becomes a natural wealth that can be relied upon in developing its areas if it is invested rationally and thoughtfully. On this basis, the groundwater in Makhmour district was studied through the natural environment which It is represented by (geographical location, geological structure, morphology, and climate in terms of (rain and temperatures), soil and natural vegetation), which all affect the quantity and quality of that water. Therefore, the objectives of the research are to highlight the validity of groundwater by studying the chemical properties of (52) samples of water wells in the district in terms of percentage of(chlorine, magnesium, potassium, calcium, nitrate, sulfate, hardness, pH and dissolved solids) and its comparison with the standards of the World Health Organization, which affects the suitability of that water for different uses, especially drinking That organization, With the exception of the pH, all of them were recorded as the internationally desirable limit, as well as the dissolved solid salts recorded 42 samples within fresh water and 10 samples within the average salinity. We also dealt with the aspects of groundwater investments in civil uses (rural and urban) and agricultural activities such as crops (legumes, industrial, grains and vegetables), livestock, fish farms, poultry fields, and various industrial uses spread in the districts of the judiciary.